Assessment method of social entrepreneurship nature and its development - Pereverzieva, Anna; Volkov, Volodymyr (Management and Entrepreneurship: Trends of Development, 2020)
The study of social entrepreneurship and the assessment of its necessity caused by socio-economic problems like low level of household purchasing power and state failure to solve is relevant. The need to introduce and develop social entrepreneurship requires favourable environment in the country, determined by state support, public acceptance and availability of potential investors. The phenomenon of social entrepreneurship in the economy has dual nature: it contributes to full satisfaction of households` basic needs and ensures social entrepreneur`s self-realization. Social enterprise provides both non-commercial and commercial activity. A non-profit component is a key one in the European model of social entrepreneurship. Assessment of nature and opportunities of social enterprises development allows to reach the principle of “need-opportunity” balance aimed at effective management decision-making regarding the expediency to introduce the form of business in the country. If there is a need for social entrepreneurship national economy demands building favourable environment for its functioning and development. The study purpose is to propose the assessment method of social entrepreneurship nature and its development and the necessity of its application around the world, to single out conditions for its development to solve socio-economic problems and move towards the economy with a human face. The study object is scientific and practical basis of social entrepreneurship development in the context of the necessity of its implementation and operating environment. Methodology: comprehensive assessment approach has been used in the study. It comprises different methods, namely: the index method (to calculate sub-indices and the overall index, to make single system design to facilitate comparison); the matrix method (grouping of countries according to their changing need for social entrepreneurship); multiplicative model (analytical toolkit to determine overall index to estimate the contribution of each indicator simultaneously). The study result is the assessment method of social entrepreneurship nature and development implemented in the EU. Conclusions: it has been determined that during 2016 and 2019, with a lag of three years, a third of European countries have changed their attitude towards social entrepreneurship. Some countries have increased their need for social enterprises, but favourable conditions for their development have not been built. Other countries have been improving environment for social enterprise activities, but their demand has been diminishing. The growing need for social enterprises in one third of the countries has been accompanied by favourable environment for their activity and development. Scientific and practical relevance is the possibility to apply the proposed method for any country or group of countries with similar level of economic development to prove the relevance of social entrepreneurship implementation as innovation form of business, to identify the terms of its advantageous development in the long period and to build the strategy of social enterprises operations and their management.JEL Classification: L31, O11, O15.